Does the stock exchange contribute to economic growth in the CARICOM Sub Region? - Thomas, Wendy-Ann ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Investigates whether the introduction of the stock exchange in Barbados, Jamaica and Trinidad and Tobago has promoted economic growth. Compares the contribution to growth of the stock market development through the coming into being of the stock exchange to that of the banking sector in Jamaica, Barbados and Trinidad and Tobago using annual time series data. Investigates the existence of reverse causality.